Godly husbands and housework: A global examination of the association between religion and men’s housework participation - Gull, Bethany (Social compass, 2020)
In studies seeking to understand cultural and institutional influences on the division of domestic labor, religion has often been left out of the picture in favor of economic, gender and welfare state context. By examining men from 34 countries using 2012 International Social Survey (ISSP) data this study explores the ways in which religion is associated with men’s household labor participation. We utilize individual measures of religiosity as well as cultural zones based on religious and cultural similarity to analyze the effect of predominant religion and religious participation on men’s housework. Differences emerge between men by religious tradition, level of religious attendance, and across cultural zones. Contrary to expectations, we find increased religious participation at the individual and cultural zone levels associated with greater participation in some housework tasks and time spent on housework, though the findings show great variation by task and religious tradition. Our findings indicate two potential paths leading to men’s increased housework participation: a nonreligious, egalitarian one, and a religious, family-centered one.